2016
DOI: 10.1016/j.jalz.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Which types of mental work demands may be associated with reduced risk of dementia?

Abstract: Our longitudinal observations suggest that dementia risk may be reduced by some but not all types of mental work demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 23 publications
2
39
1
5
Order By: Relevance
“…The results of the present study are in contrast with earlier findings, suggesting an association between work complexity and dementia [6][7][8][9][10][11], although some researchers report findings similar to ours [12]. Our results also correlate fairly well with research examining cognitive change in old age and those who find only an association between level of cognitive performance and occupational complexity at baseline, but no association between occupational complexity and cognitive change [25,26].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The results of the present study are in contrast with earlier findings, suggesting an association between work complexity and dementia [6][7][8][9][10][11], although some researchers report findings similar to ours [12]. Our results also correlate fairly well with research examining cognitive change in old age and those who find only an association between level of cognitive performance and occupational complexity at baseline, but no association between occupational complexity and cognitive change [25,26].…”
Section: Discussioncontrasting
confidence: 81%
“…According to the cognitive reserve hypotheses, high mental demands at work would facilitate the development of cognitive skills because individuals would continue to hone their cognitive skills when they are exposed to cognitive challenging environments; further, many studies have also reported support for this hypothesis [6][7][8][9][10][11]. For example, by using data from the Swedish Twin Registry, Andel and colleagues [6] divided the complexity of work into three categories, including level of working with data (e.g., analyzing), people (e.g., mentoring), and things (e.g., precision working).…”
Section: Introductionmentioning
confidence: 99%
“…Education seems to be a factor contributing to a better cognitive reserve [7,26,27]. Studies have shown that high occupational demands preserve cognitive functioning and reduce dementia risk, indicating that occupational activities designed to challenge executive cognitive functions and information processing abilities also seem to increase cognitive reserve [28][29][30]. Cognitive interventions designed to improve reasoning abilities (in contrast to processing speed, memory, and no intervention) may also contribute to a better cognitive reserve because they not only improve cognitive functioning, but also significantly improve functioning in daily life (i.e., diminish dementia symptomatology [31,32]).…”
Section: Attributes Of Cognitive Processes Of Cognitive Reservementioning
confidence: 99%
“…These include the inadequacy of current treatments to alleviate the symptoms of the disease. Also, the difficulty in developing novel interventions to detect [1–57], delay [58–69], or halt disease progression continues to be an important hurdle. The well‐recognized public health and economic imperative [70–83] posed by the disease continues to be an important motivator to communicate new knowledge across multiple disciplines that will help increase the likelihood of unlocking the complexity of neurodegeneration [84–90] associated with many dementing illnesses.…”
mentioning
confidence: 99%